LOCAL COMPLICATIONS AFTER INFERIOR GINGIVAL CARCINOMA SURGERY - Mitani, Hiroko; Yonekawa, Hiroyuki; Kamata, Shin-etsu (JIBI INKOKA TEMBO, 2006)
Since radical treatment is accompanied by regional and extensive tissue resection in advanced inferior gingival carcinoma, head and neck reconstruction is relatively difficult. If a surgical complication such as a fistula develops, the grafted bone-plate may be contaminated by saliva and wound healing impeded by compound factors such as poor blood circulation in the remaining mandibula and surrounding tissues due to inflammation. Subjects were 50 patients undergoing osseous scirrhous reconstruction for inferior gingival carcinoma from 1986 to 2004. Of the 50 cases, 15 cases had local postoperative complications, with 4 requiring reoperation and the remaining 11, including 2 of flap necrosis, cured conservatively. Cases were classified into group A, with no bloodstream involvement due to bone bloodstreams of reconstruction materials, group B, involving bloodstreams from the periosteum, and group C, with direct nutrient vessel in the bone. Complications occurred in 27% in group C, versus 35% in groups A + B, the difference in incidence being very small. Reoperation was only 3% in group C, Versus 18% in groups A + B. The incidence of complications was 42% for the flap of the latissimus dorsi with ribs versus 29% for the scapular flap. Reoperation was 17% for the latissimum dersi versus 3% for the scapular flap. Infections are this liable to be prolonged. Reflecting on complications in hard reconstruction of the mandibula, we studied surgical technique and matters necessary to make hard reconstruction successful.